PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KETERAMPILAN MENULIS TEKS EKSPOSISI - Asyiqin, Nurul; Ratna, Ellya; Hafrison, Mohd. (Universitas Negeri Padang, 2018)
There are three purposes of this study. First, describe the writing skill level of exposition text of VIII studentsMTsN 2 Padang before using problem based learning (PBL) model. Second, describe the writing skill level of exposition textofVIII students MTsN 2 Padang after using problem based learning (PBL) model. Third, describe the influence of problem based learning (PBL) model onwriting skillof exposition text of VIII students MTsN 2 Padang. This research type is quantitative with experiment method. Based on data analysis, the use of problem based learning (PBL) model has an effect on writing skil of exposition text of VIII students of MTsN 2 Padang.Â Kata kunci: model problem based learning, menulis, teks eksposisi